UMUMTA’LIM MAKTABLARIDA KIMYOVIY TILNING AHAMIYATI VA VAZIFALAR USTUVORLIGI SIFATIDA - Kosnazarov, S.T.; Kaipbergenov, A.T. (SCIENCE and SOCIETY, 2019)
A chemical language is usually represented by symbols or replaces something or an event used to transmit or transmit information about signs, objects, or events. Language is reflected in to science, primarily as terminology. A term is a word or combination of words that expresses a particular understanding of science, technology and art.
Keywords: chemical language; terms; chemical terminology; symbolism; nomenclature